An inductive qualitative approach to explore Nurse Practitioners views on leadership and research: An international perspective. Issue 13 (16th April 2019) - Ryder, Mary; Jacob, Elisabeth; Hendricks, Joyce
Abstract: Aims and objectives: To explore the ways in which Irish and Australian Nurse Practitioners (NPs) implement leadership and research in their roles and whether there is a difference in how leadership and research are demonstrated between NPs in Ireland and Australia. Background: The original concept of the NP role was to expand nursing practice in order to provide high‐quality, accessible health care to patients. This placed NPs at the crux of changes to healthcare delivery. Implementing these changes requires leadership. Research demonstrates the effects of these changes to healthcare delivery and contributes to healthcare knowledge from the nursing profession. Design: In the qualitative phase of a mixed methods study, an interpretative descriptive approach was used to draw on participant experiences. Methods: Thirty‐eight respondents agreed to be interviewed following an online survey. Ten interviews were recorded and transcribed verbatim. Data were analysed using Braun and Clarke thematic analysis method. The research complied with the consolidated criteria for reporting qualitative research, COREQ. Results: Ten participants, five NPs from Ireland and five from Australia were interviewed. Four themes emerged from the analysis: (a) Innovative leadership, which included the categories of leadership activities, the work of NPs and trailblazers; (b) Optimism, incorporating pride in achievements, the future outlook for the role and continued innovation of NPs over time; (c) Research, which included the NP research role, research challenges, support and research leadership; and (d) Resilience, which included overcoming resistance, isolation and seeking positive support systems. Conclusion: Nurse Practitioners are clinical leaders focused on improving healthcare delivery for patient populations. There is a lack of understanding of the NP role. Nurse Practitioners lack confidence to be independently research active. Research by NPs requires support from nurses in academia. There is no difference in the role in Ireland and Australia. Relevance to clinical practice: Nurse Practitioners are engaged in healthcare transformation. Nurse Practitioners require support from research experts in academia to make a significant contribution to nursing knowledge in healthcare delivery.